Quality of life and mental disorders in caregivers of children with special needs - Talita Cristina Pegorin; Marcela Martins Furlan de Léo; Samuel Spiegelberg Zuge; Crhis Netto de Brum; Lisiane da Rosa; Vander Monteiro da Conceição (Universidade Federal do Ceará, 2021)
Objective: to analyze the relationship between quality of life and presence of common mental disorder in caregivers of children who need special health care. Methods: cross-sectional study with 87 caregivers of children with special health care needs. A sociodemographic questionnaire, the World Health Organization Quality of Life-bref and the Self-Reporting Questionnaire were used. Descriptive statistical analyses were performed based on frequencies and inferential with Mann-Whitney, Kruskal-Wallis and Spearman's Correlation Coefficient tests. Results: mean rank differences were found in the relationship between responsible caregiver and common mental disorder; caregiver has some grievance, undergoes psychopharmacological treatment and psychological monitoring and the physical and general domains of quality of life and common mental disorder. Moreover, there was an inverse correlation between the domains of quality of life and common mental disorder. Conclusion: the lower the socres in the quality of life domains, the higher the development of common mental disorder in caregivers.